Edukasi Tentang Reproduksi Sehat Pada Remaja di Desa Ladang Peris Kabupaten Batanghari - Lusiatun Lusiatun; Anna Waris Nainggolan; Imarina Tarigan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. Adolescence is a transitional period from childhood to adulthood, where rapid physical growth and reproductive organ maturation occur. The purpose of this community service activity is to provide education about healthy reproduction to adolescents so that they can understand the development of adolescent reproductive organs, can prevent and protect themselves from things that will harm their reproductive health. This community service was carried out by gathering adolescents in RT10 Ladang Peris Village, Batanghari Regency. The adolescents who had attended underwent a health check-up in the form of weight and blood pressure measurements, filling out a pre-test questionnaire, followed by a presentation of material on adolescent reproductive health, participant evaluation with questions and answers and filling out a post-test questionnaire. After the healthy reproductive health education was carried out, adolescents obtained a significant increase in knowledge compared to before being given education with an average knowledge level score before the material presentation of 73,81 and after the material presentation of 93,45. Keywords: Adolescence; Healthy Reproduction; Puberty. Abstrak. Remaja merupakan masa transisi dari anak-anak menuju dewasa, yang akan mengalami pertumbuhan fisik yang cepat dan akan terjadi pematangan organ reproduksinya. Tujuan kegiatan pengabdian kepada masyarakat ini adalah untuk memberikan edukasi tentang reproduksi sehat pada remaja sehingga dapat mengetahui tentang perkembangan organ reproduksi remaja, dapat mencegah dan melindungi diri dari hal-hal yang akan merugikan kesehatan reproduksinya. Pengabdian masyarakat ini dilakukan dengan mengumpulkan remaja yang berada di RT10 Desa Ladang Peris Kabupaten Batanghari. Remaja yang telah hadir dilakukan pemeriksaan kesehatan berupa pengukuran berat badan dan tekanan darah, mengisi kuesioner pretest, dilanjutkan dengan pemaparan materi tentang kesehatan reproduksi remaja, evaluasi peserta dengan tanya jawab dan pengisian kuesioner posttest. Setelah dilakukan edukasi kesehatan reproduksi sehat pada remaja didapatkan peningkatan pengetahuan yang signifikan dibandingkan sebelum diberikan edukasi dengan rata-rata nilai tingkat pengetahuan sebelum pemaparan materi sebesar 73,81 dan setelah pemaparan materi sebesar 93,45. Kata Kunci: Pubertas; Remaja; Reproduksi Sehat.